2011
DOI: 10.1002/pssc.201000973
|View full text |Cite
|
Sign up to set email alerts
|

Study of excess carrier dynamics in polar, semi‐polar, and non‐polar (In,Ga)N epilayers and QWs

Abstract: We studied carrier recombination and diffusion in GaN/sapphire templates, (In,Ga)N layers, and (In,Ga)N quantum well structures oriented along the polar [0001], semi‐polar [11‐22], and non‐polar [11‐20] orientations by means of light induced transient grating, differential transmission, and photoluminescence optical techniques. We show that the lifetime of excess carriers drops by orders of magnitude when changing the orientation from polar to non‐polar, both in GaN templates and (In,Ga)N layers. We attribute … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…This field reduction has been theoretically predicted to increase overlap between electron and hole wave-functions resulting in an increased radiative recombination probability, which may enhance the performance of LEDs based on semipolar nitrides. However, this prediction needs to be further confirmed experimentally [3][4][5][6].…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…This field reduction has been theoretically predicted to increase overlap between electron and hole wave-functions resulting in an increased radiative recombination probability, which may enhance the performance of LEDs based on semipolar nitrides. However, this prediction needs to be further confirmed experimentally [3][4][5][6].…”
Section: Introductionmentioning
confidence: 94%
“…This has been linked to the efficiency droop in the polar QWs. For (112̅ 2) InGaN/GaN QWs, to our best knowledge, only a few studies on the effect of ELZ on radiative recombination lifetimes have been performed by time-resolved photoluminescence for (112̅ 2) QWs [3,5,6]. By measuring the Stokes-shift, Zhang et al [6] have reported that a larger polarization field of polar QWs mainly causes a larger shift than (112̅ 2) QWs.…”
Section: Introductionmentioning
confidence: 99%